EFFECTIVENESS OF FUNCTIONAL KNEE BRACING FOLLOWING ACL RECONSTRUCTION: A NARRATIVE REVIEW - Klaudia Malec,; Amin Omidi,; Katarzyna Majewska,; Monika Ziemba,; Michał Stasiak,; Wiktor Żyro,; Katarzyna Żyro,; Adam Woźniak,; Karolina Woźniak,; Franciszek Glapiński, (International Journal of Innovative Technologies in Social Science, 2025)
Anterior cruciate ligament (ACL) reconstruction is a frequently performed orthopedic procedure, especially among physically active individuals. Postoperative use of functional knee braces is still a topic of debate, due to the mixed findings about their clinical value. This review aims to evaluate the reasons for brace use following ACL reconstruction based on current scientific evidence, focusing on clinical outcomes, biomechanical factors, proprioception, and the risk of reinjury. The findings indicate that use of functional braces does not result in significant advantages over rehabilitation alone in most cases. Braces seem to have minimal effect on joint stability, range of motion, muscle strength, or time to return to sport. Nonetheless, particular patient subgroups - such as young athletes, individuals with poor neuromuscular control, or those engaged in pivot-heavy sports - may benefit from bracing. In such cases, braces might enhance proprioception, reduce shear forces during activity, and provide psychological reassurance. Some studies also suggest a potential role in reinjury risk reduction, especially with prolonged use lasting from six to twelve months. Recent innovations in brace design, such as dynamic bracing systems, may further improve their clinical applicability. In conclusion, the evidence does not support routine brace use for all patients following ACL reconstruction. Instead, brace prescription should be individualized, and tailored to the patient's functional demands, activity level and reinjury risk. Further high-quality studies with long-term follow-up are needed in order to refine recommendations and to better define the role of bracing in postoperative rehabilitation.